ACCURATE TIME-DEPENDENT WAVE PACKET STUDY OF THE H++LiH REACTION AT EARLY UNIVERSE CONDITIONS - Aslan, E.; Bulut, N.; Castillo, J. F.; Banares, L.; Aoiz, F. J.; Roncero, O. (Iop Publishing Ltd, 2012)
The dynamics and kinetics of the H+ + LiH reaction have been studied using a quantum reactive time-dependent wave packet (TDWP) coupled-channel quantum mechanical method on an ab initio potential energy surface at conditions of the early universe. The total reaction probabilities for the H+ + LiH(nu = 0, j = 0) -> H-2(+) + Li process have been calculated from 5 x 10(-3) eV up to 1 eV for total angular momenta J from 0 to 110. Using a Langevin model, integral cross sections have been calculated in that range of collision energies and extrapolated for energies below 5 x 10(-3) eV. The calculated rate constants are found to be nearly independent of temperature in the 10-1000 K interval with a value of approximate to 10(-9) cm(3) s(-1), which is in good agreement with estimates used in evolutionary models of the early universe lithium chemistry.
Keywords: astrochemistry; early universe; ISM: molecules; methods: numerical; molecular processes